A redox-responsive mesoporous silica nanoparticle with a therapeutic peptide shell for tumor targeting synergistic therapy. Issue 37 (12th September 2016) - Xiao, Dong; Hu, Jing-Jing; Zhu, Jing-Yi; Wang, Shi-Bo; Zhuo, Ren-Xi; Zhang, Xian-Zheng
Abstract : A novel redox-responsive mesoporous silica nanoparticle (MSN) based nanocarrier, which is capped with a therapeutic peptide ((RGDWWW)2 KC) containing an RGD target motif, is reported for tumor targeting synergistic therapy. Abstract : In this study, we report a novel redox-responsive mesoporous silica nanoparticle (MSN)-based nanocarrier, capping with a therapeutic peptide ((RGDWWW)2 KC) containing a RGD target motif, for tumor targeting synergistic therapy, which is designated as TTSTMSN. The MSN was decorated with a tumor-targeting therapeutic peptide as a potential gatekeeper. The two branched peptides containing rich tryptophans allowed the pores to be blocked via π–π stacking and hydrophobic interactions. Once the drug loaded nanoparticles were taken up by the cancer cells through integrin-mediated endocytosis, the therapeutic peptide capping shells on the surface of MSNs were released, inducing the loaded drug to diffuse into the cytoplasm after breaking of the disulfide bonds, triggered by the high concentration of glutathione (GSH) in cancer cells. At the same time, the falling therapeutic rich tryptophans in the branched chains interacted with DNA due to the indole rings, leading to disturbance of the DNA structure through the strong π interactions and causing cell apoptosis. There is no such report on capping of drug loaded porous silica with a therapeutic peptide shell, co-delivering an anticancer drug and therapeutic agent for tumor targeting synergistic therapy, which will have great potential in developing multifunctional nanocarriers based on therapeutic peptides for synergistic treatment.